Aprendizagem significativa em uma abordagem no ensino de circuitos elétricos no ensino médio - Silva, Jonnathan da (2020)
This study proposes an educational product, which arose from how to stimulate student participation in physics classes, through practical/experimental activities. The main objective was appropriation, by the students, of the basic concepts of electrical circuits, related to electrostatics. We sought to encourage the involvement of students in classes; make physics teaching more dynamic; present the concept of electrical circuits in order to instigate students' knowledge. The educational product was developed with two classes from the 3rd series of High School at night, from Colégio Estadual Ipê Roxo, of the city of Foz do Iguaçu-PR, with the participation of an average of forty-eight students. In order to corroborate for a meaningful learning, from the students' previous knowledge, taking an experimental approach, using materials that have a low market value, when comparing with the kits that we find available on the market. The applied educational product was accepted by the students, arousing interest in the content and participation was satisfactory, leading us to realize that practical/experimental activities can be a good strategy for teaching physics, being an alternative for the teacher teaching, in addition to traditional classes.